(untitled) (The International Journal for Scientific Research, 2024)
The subject of the discretionary power of the subject judge regarding the assessment of serious error requires the judge before whom the dispute is brought to examine the reasons relied upon by the employer to make the decision to dismiss the worker and give them the legal qualification that is consistent with the requirements of the Labor Law, which determines the conditions and sets the framework for terminating the employment relationship so that the employer does not abuse his voluntary right, whether by verifying the seriousness of the error committed by the worker, or by assessing the reason and justification for the dismissal. Hence, the question revolves around the criteria for assessing gross error and the authority of the subject judge to assess whether the error is gross or simple, and the scope of the supervisory authority of the Supreme Court regarding assessing the justification for gross error or not? The exercise of discretionary power requires the judge to first verify the existence of the reason for dismissal in itself, then if it is proven to have been achieved by the means stipulated by the law, he tends to exercise judicial oversight over arbitrary dismissal from an objective standpoint, by assessing the seriousness of the error committed by the worker, as a justification and reason on which the employer relied in dismissing the worker.